Larutan pencuci hidung salin isotonis tidak terbukti mempercepat waktu transpor mukosilia pada pasien dengan rinosinusitis akut di RSUP Sanglah, Bali, Indonesia - Ni Putu Oktaviani Rinika Pranitasari; Luh Made Ratnawati; I Nyoman Adiputra (DiscoverSys Inc., 2020)
Background: Mucociliary clearance is a significant element of the defence system of the entire respiratory tract. Impairment of the mucociliary clearance serves as a medium for sinonasal infections. Saline nasal irrigation is believed to alleviated rhinosinusitis symptoms by clearing excess mucus, reducing congestion and remove infectious materials from the inspired air. This study aimed to determine the efficacy of mucociliary transport time of isotonic saline nasal solutions in patients with acute rhinosinusitis.Methods: An experimental study using pre- and post-test with control group design was conducted in this study. Mucociliary transport time was measured by the saccharine test on 20 acute rhinosinusitis patients before and after 7 days’ treatment with intranasal isotonic saline solutions and standard therapy (ciprofloxacin, pseudoephedrine/ triprolidine, ambroxol) for the case group and standard treatment for the control group. Data were analysed using SPSS version 20 for Windows.Result: The average mucociliary transport time before therapy was 35.5±10.7 minutes and 29.2±7.7 minutes for the case group and control group, respectively. The average mucociliary transport time after therapy was 22.9±8.7 minutes and 18.0 ± 5.6 minutes for case group and control group, respectively. The mean difference mucociliary transport time before and after therapy was 11.0±7.5 minutes and 9.4±5.3 minutes for the case and control group, respectively (p=0.499).Conclusions: The addition of intranasal isotonic saline solutions in acute rhinosinusitis patients has the same effect of mucociliary transport time with oral medication with the antibiotic, decongestant, and mucolytic without intranasal isotonic saline solutions. Latar Belakang: Transpor mukosilia merupakan salah satu mekanisme pertahanan saluran pernapasan. Adanya gangguan pada sistem tersebut menjadi predisposisi terjadinya infeksi sinonasal. Larutan pencuci hidung dengan salin isotonis dipercaya dapat mengurangi gejala akibat rinosinusitis dengan cara membersihkan sekret, mengurangi odema dan mengeluarkan bahan-bahan berbahaya yang masuk bersama udara pernapasan. Tujuan penelitian ini adalah untuk menilai efektivitas waktu transpor mukosilia larutan pencuci hidung salin isotonis pada pasien rinosinusitis akut.Metode: Uji eksperimental dengan desai pre-post test dengan kontrol dilakukan pada penelitian ini. Waktu transpor mukosilia diukur menggunakan uji sakarin terhadap 20 pasien rinosinusitis akut sebelum dan 7 hari sesudah pemberian larutan pencuci hidung salin isotonis dan terapi standar (ciprofloxacine, pseudoephedrine/triprolidine, ambroxol) pada Kelompok Perlakuan dan terapi standar pada Kelompok Kontrol. Data dianalisis menggunakan SPSS versi 20 untuk Windows.Hasil: Rerata waktu transpor mukosilia sebelum perlakuan pada Kelompok Perlakuan adalah 35,5 ± 10,7 menit dan 29,2 ± 7,7 menit pada Kelompok Kontrol. Rerata waktu transpor mukosilia sesudah terapi adalah 22,9 ± 8,7 menit dan 18,0±5,6 menit berturut-turut pada Kelompok Perlakuan dan Kelompok Kontrol. Median selisih waktu transpor mukosilia sebelum dan sesudah terapi adalah 11,0±7,5 menit pada Kelompok Perlakuan dan 9,4 ± 5,3 menit pada Kelompok Kontrol (p=0,499).Kesimpulan: Penambahan larutan cuci hidung salin isotonis pada rinosinusitis akut memiliki efek waktu transpor mukosilia yang sama dengan pemberian antibiotika, dekongestan dan mukolitik tanpa larutan cuci hidung salin isotonis.